Economic Growth Though Competitive Advantage and Specialization: The Example of Winemaking in Moldova (European Journal of Marketing and Economics, 2024)
This article addresses growth through economic specialization based on completive advantage. Winemaking is one of the key branches of Moldova’s economy, which stands for about 20 percent of Moldova’s GDP. It has high potential in terms of contribution to qualitative economic growth. About 90 percent of Moldovan wine is intended for export to countries like Great Britain, Germany, Czech Republic, Poland, Greece, Scandinavia, US, Japan and China, and only 10 percent for local consumption. Winemaking is one of Moldova’s specialties, which enjoys long-lived traditions and vivid history of Moldova’s wineries, including Milesti Mici registered in 2005 as world’s biggest winery by Guinness World Records. The concept of this study suggests that economic growth must be induced through competitive areas of specialization, which are present in any economy. Substantial investments are required to develop those areas. Structurally, winemaking branch in Moldova is comprised of small and medium enterprises flexible and open to innovation, which is a strong prerequisite to develop those areas into drivers of economic growth eventually resulting into new jobs, higher export, higher GDP, better living conditions. Winemaking alone cannot be the answer to Moldova’s economic problem. Yet, this study highlights the importance of focusing on competitive advantage and specialized growth to create qualitative internally-driven economic growth, particularly important for nations struggling within current socio-economic affairs.
Keywords: Economic Growth, Competitive, Advantage, Specialization, Winemaking, Moldova